Preliminary Methodology for the Integration of Lean Construction, BIM and Virtual Reality in the Planning Phase of Structural Intervention in Heritage Structures - Brioso, X.; Calderón-Hernandez, C.; Aguilar, R.; Pando, M.A. (Springer Netherlands, 2019)
The main purpose of this article is to describe a proposed methodology to integrate modern construction management tools and procedures such as Lean Construction (LC), Building Information Modeling (BIM), and Virtual Reality (VR) in the planning phase of structural intervention of heritage structures. The proposed methodology that integrates these techniques is referred to as Lean Project Delivery System (LPDS). This paper explains the main principles, tools, techniques, practices and technologies, like VR, laser scanner, and photogrammetry that integrated result in synergy with the design, and planning components of the selection of the structural retrofitting alternatives. The proposed method associates the workflow design, workflow execution, LPDS elements and Management of Heritage Structures (MHS) requirements. The proposed LPDS methodology is applied to the St. Jerome Hall, a sector of the Church of the Nativity, located in Bethlehem, Palestine where the selection of the most feasible structural consolidation technique was required to retrofit this area due to some archaeological excavations. The conclusions drawn from the application of the proposed methodology to this case history may have some biases due to unique constraints in this project related to regional and project specific considerations. However, the paper hopes to contribute by providing an integrated framework for modeling and planning that can improve the state of practice in this area of knowledge.
Keywords: Workflow; Engineering; Building information modeling; Systems engineering; Virtual reality; Photogrammetry; Construction engineering; Computer science; Operations management; Scheduling (production processes); https://purl.org/pe-repo/ocde/ford#2.01.03